Investigation Of Base And Wall Pressure In Suddenly Expanded Flow Through Ducts Using Ribs As Passive Flow Control - Sethuraman, Vigneshvaran (2019)
Suddenly expanded flows play a vital role in many important applications in the fields of automobiles, trains, aircraft, rockets, missiles and space vehicles. Base drag is a common problem that hinders the performance in the above-mentioned applications, and contributes significantly to the total drag. The base pressure which exists in flows over a body at the rear is responsible for base drag which is a considerable proportion of the total drag. There are situations where the base pressure has to be increased to reduce base drag and decreased to achieve better fuel mixing in combustion processes. It becomes necessary then to control the base pressure depending upon the application. An analysis of the control of base pressure in suddenly expanded supersonic flows in a rectangular duct is presented. The base pressure is altered by placing ribs of different heights at specific locations along the length of the duct. Ribs of 3 different heights namely 10%, 16% and 23% of the duct height have been used. Each rib was in turn placed at 0.283H, 1.75H and 2.75H along the length of the duct. The setup was tested in Mach numbers of 1.00, 1.36, 1.64 and 2.01 individually. The interaction of secondary vortices due to the presence of ribs placed at different locations and varied heights with the primary vortex at the nozzle exit, is the main factor altering the base pressure either increase or decrease. It is observed that the base pressure decreases initially with increase of nozzle pressure ratio (NPR) in overexpanded flows and exhibits an increase in underexpanded flows. The distribution of wall pressure exhibits fluctuations with base pressure increase in the presence of ribs. These observations have been supported by quantitative data as percentage increases above the base values. The corresponding effect on the wall pressure distribution due to placing of ribs of different heights and locations in the duct have also been quantified. With the placement of ribs, increases in base pressure as high as 57% for rib height (h/H) of 0.23 and wall pressure fluctuations up to 30% for the same height were observed. A rib height of about 10% of the duct height placed not far from the nozzle exit in underexpanded flows yields sufficiently high values in base pressure without undue fluctuations in wall pressure distribution along the duct. In high-speed vehicles such as rockets and missiles, the existence of base drag leads to reduction in performance efficiency. This problem also calls for controlling of jets which can assist in improving the performance characteristics of these vehicles. In combustion chambers, an increased level of local turbulence due to sudden expansion of the fluid leads to improper fuel mixing conditions thereby, increasing specific fuel consumption (SFC) and higher operational costs. Commercial data acquisition system has been used in the present study while the design of a cost-effective DAQ accommodating more channels has been included. The present work suggests feasible methods of overcoming problems in realistic situations with minimal changes in configuration and costing.